2014
DOI: 10.5761/atcs.cr.12.02098
|View full text |Cite
|
Sign up to set email alerts
|

A Resected Melanoma of the Lung Metastasized from an Occult Skin Lesion: A Case Report

Abstract: An 86-year-old woman with a history of right breast cancer resected seven years ago had a small pulmonary nodule located in left S5. Diagnosis was made by bronchoscopy using the endobronchial ultrasonography-guided sheath (EBUS-GS) method, but a histological diagnosis was not obtained. Wedge resection was performed due to suspicion of a metastatic lesion from breast cancer based on radiological findings. The tumor was subsequently found to be malignant melanoma of the lung. An initial diagnosis of primary mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However the importance of a full physical examination, including oral cavity, cannot be overemphasized [ 11 ]. Similar to this case, however, it can take up to 8 months to locate the primary melanoma [ 12 ]. It is hypothesized that some lesions diagnosed as primary pulmonary melanomas are, in fact, metastases from occult primary lesions which have undergone spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%
“…However the importance of a full physical examination, including oral cavity, cannot be overemphasized [ 11 ]. Similar to this case, however, it can take up to 8 months to locate the primary melanoma [ 12 ]. It is hypothesized that some lesions diagnosed as primary pulmonary melanomas are, in fact, metastases from occult primary lesions which have undergone spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed physical examination revealed a black tumor in the oral cavity, and this was suspected to have been the primary. Shimmyo et al also demonstrated a case of malignant melanoma that primary lesion was detected 8 month after resection of lung metastasis 2 . In view of the rarity of primary lung melanoma, physical examination of the entire skin and mucosa, including the oral cavity, was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Shimmyo et al also demonstrated a case of malignant melanoma that primary lesion was detected 8 month after resection of lung metastasis. 2 In view of the rarity of primary lung melanoma, physical examination of the entire skin and mucosa, including the oral cavity, was necessary. Although positron emission tomography (PET) scanning is useful for detecting malignant diseases, we were unable to detect the primary tumor by PET preoperatively in this case.…”
Section: Discussionmentioning
confidence: 99%